‘Dare not to know’: the right not to know genetic information - Koukouzelis (Κώστας Κουκουζέλης) Kostas (Bioethica, 2019)
The paper aims to make a contribution to the ongoing discussion regarding the right not to know genetic information. Even though such a right is currently acknowledged in a series of legal documents, neither its recognition, not its normative grounding is always clear or unanimously accepted. After presenting a number of arguments against the right not to know, I will make an effort to offer a persuasive normative grounding. During the course of this effort I will argue that when there is a case of available genetic information regarding especially healthy individuals, such a right should be normatively grounded on autonomy and respect for the person’s privacy. Genetic information, especially when comes up as incidental findings, does not carry, most of the times, certainty, but involves probability. In other circumstances genetic information is of no use to the individual, because there is no treatment available at the time. Finally, respect for the person and her privacy makes genetic counseling of great importance, under current circumstances.